ANALISIS PROFITABILITAS WANATANI (AGROFORESTRY) BERBASIS KARET KLON DALAM BERBAGAI AGROEKOLOGI DI DESA KARANG SAKTI KECAMATAN MUARA SUNGKAI KABUPATEN LAMPUNG UTARA - Raisika, .; Arifin, Bustanul; Abidin, Zainal (Lampung University)
This research intends to determine the profitability of rubber agroforest farmng and to compare the profitability status among different agroecological system in Karang Sakti Village of Muara Sungkai Sub-district, North Lampung, Lampung Province. The study employs survey method and the data was analyzed using two way anova and further analyzed using crosstabulation analysis The study selects 38 rubber agroforest farmers randomly.. The study shows that the highest profitability of rubber based agroforest system with intercropping of corn and cassava located in middle agroecological location, earning NPV at Rp 23.348.476. All agroforest systems on all agroecological locations are profitable, thanks to good prices of most commodity. Statistics analysis suggests that there is no profitability difference of all agroecological locations. This suggest that the agroecosystem in the study area was not sensitive to different agroecology meaning, it is applicable to any agroecology system within the boundary of study site.